SYNTHESIS AND CHARACTERIZATION OF NANOSILICA (SiO2) VOLCANIC ROCK OF MOUNT BATUR IN BALI - Artha, I Komang Restu Widi; Mardana, Ida Bagus Putu; Arjana, I Gede (Indonesian Physical Review, 2024)
This research was conducted to synthesize and characterize silica minerals (SiO2) from volcanic rocks in the active volcano in Bali, namely Mount Batur. The synthesis carried out on five different color variants of this rock sample is by the coprecipitation method which begins with the process of taking rock samples on Mount Batur, crushing the rock until it becomes powder with a size of 100 mesh, washing with distilled water and drying, immersing the rock powder in the solution. 2 M HCl for 12 hours, then the results of the soaking were reacted again with 7 M NaOH solution as a hydrolysis process to obtain pure SiO2 in the sample. In the form of sodium silicate precursor (Na2SiO3), the sample was titrated with a 2 M HCl solution to obtain silica gel which was then washed and dried until amorphous silica powder was produced. The results of the XRF analysis showed that the SiO2 mineral content in the sample after going through the synthesis process was 94.9% and the Si element was 89.9%. The XRD characterization results show that the phase formed from the sample has a quartz structure with the highest peak at an angle of 2θ = 23.07o, then decreases and levels out at an angle of 2θ = 32.94o which is characteristic of an amorphous structure and with a silica grain size of 8.47 nm – 8.65 nm.